DETERMINASI PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS - Sri Dewi Anggadini; Rini Herdiani (Universitas Padjadjaran, 2020)
This research was conducted at various industry companies listed on the Indonesia Stock Exchange 2014-2018. The phenomenon that occurs is an increase in company working capital turnover, but the company's profitability decreases. The purpose of this study is to learn more about working capital turnover towards profitability in various industry companies listed on the Indonesia Stock Exchange 2014-2018. This research uses descriptive analysis method and verification method using quantitative analysis. The population used in this study is the financial position financial statements and earnings reports of various industrial companies listed on the Indonesia Stock Exchange 2014-2018. Sampling with purposive sampling technique with data of 5 years. The statistical method used is multiple linear regression analysis using the SPSS 21.0 application assistance program. The results of the study showed that the working capital turnover had a significant effect on profitability in various industry companies listed on the Indonesia Stock Exchange 2014-2018.